Data from: Genome-wide support for incipient Tula orthohantavirus species within a single rodent host lineage - Labutin, Anton; Heckel, Gerald (Zenodo, 2024)
Evolutionary divergence of viruses is most commonly driven by co-divergence with their hosts or through isolation of transmission after host-shifts. It remains mostly unknown, however, whether divergent phylogenetic clades within named virus species represent functionally equivalent byproducts of high evolutionary rates or rather incipient virus species. Here, we test these alternatives with genomic data from two widespread phylogenetic clades in Tula orthohantavirus (TULV) within a single evolutionary lineage of their natural rodent host, the common vole Microtus arvalis. We examined voles from 42 locations in the contact region between clades for TULV infection by RT-PCR. Sequencing yielded 23 TULV Central North and 21 TULV Central South genomes which differed by 14.9-18.5% at the nucleotide and 2.2-3.7% at the amino acid level without evidence of recombination or reassortment. Geographic cline analyses demonstrated an abrupt (<1 km wide) transition between the parapatric TULV clades in continuous landscape. This transition was located within the Central mitochondrial lineage of M. arvalis and genomic SNPs showed gradual mixing of host populations across it. Genomic differentiation of hosts was much weaker across the TULV Central North to South transition than across the nearby hybrid zone between two evolutionary lineages in the host. We suggest that these parapatric TULV clades represent functionally distinct, incipient species which are likely differently affected by genetic polymorphisms in the host. This highlights the potential of natural viral contact zones as systems for investigating of the genetic and evolutionary factors enabling or restricting the transmission of RNA viruses. Funding provided by: Swiss National Science Foundation Crossref Funder Registry ID: https://ror.org/00yjd3n13 Award Number: 31003A_176209 Genotyping of host nuclear DNA Genome-wide nuclear DNA (nucDNA) was used to infer the genetic structure of hosts via Genotyping by Sequencing (GBS) (Elshire et al., 2011). We ...